Pollinivory and the diversification dynamics of bees. (14th November 2018) - Murray, Elizabeth A.; Bossert, Silas; Danforth, Bryan N.
Abstract : Pollinivory—the consumption of pollen rather than arthropod prey—is a defining feature of bees (Anthophila; the flower lovers). In virtually all bee species, larvae consume a diet composed of pollen mixed with nectar or floral oils. Bees arose from within a group of solitary, carnivorous, apoid wasps in the Early to Mid-Cretaceous, coincident with the rapid rise of flowering plants. It is assumed that the switch from carnivory to pollen-feeding was a key innovation that led to the rapid diversification of bees, but this has never been examined empirically. Here, we explore the hypothesis that pollinivory led to the increased diversification of bees. In contrast to common perception, we find that the switch to pollen-feeding per se does not explain their extensive diversification. Rather, our results indicate that pollinivory was a necessary but not sufficient condition for diversification, and that other complementary innovations, such as a broadening of host-plant diet, allowed the diversification of the major bee lineages. Our results have broad implications for understanding tempo and mode of bee diversification dynamics in light of their floral resources.